2016
DOI: 10.1194/jlr.d061432
|View full text |Cite
|
Sign up to set email alerts
|

Multiple apolipoprotein kinetics measured in human HDL by high-resolution/accurate mass parallel reaction monitoring

Abstract: This article is available online at http://www.jlr.org usually determines isotope enrichment by measuring the derivatized forms of D0 and trideuterated leucine (D3-Leu) ( 2, 3 ), a method with high cost and low sensitivity and specifi city. Recently, proteomics-based triple quadrupole multiple reaction monitoring (MRM) permitted a more practical and highly specifi c multipeptide approach to in vivo kinetic studies ( 4, 5 ). However, MRM relies on low-resolution readouts (unit mass resolution) that do not readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(140 citation statements)
references
References 63 publications
(67 reference statements)
10
130
0
Order By: Relevance
“…Changes in apolipoprotein abundance can now be readily assessed using one or more of a number of strategies including label-free and label-based strategies. (56,57). Quantitative proteomics provides several innovative workflows that are poised to address many of the unknowns of apolipoprotein function and metabolism.…”
Section: Hdl-c Hypothesismentioning
confidence: 99%
“…Changes in apolipoprotein abundance can now be readily assessed using one or more of a number of strategies including label-free and label-based strategies. (56,57). Quantitative proteomics provides several innovative workflows that are poised to address many of the unknowns of apolipoprotein function and metabolism.…”
Section: Hdl-c Hypothesismentioning
confidence: 99%
“…Label-free employs either spectral counting (the total number peptide-spectrum matches per protein) or the area under the curve of the peptides’ chromatographic peaks [2], under the observation that the more abundant a protein is in the sample, the more likely its peptides are detected and sequenced (Fig. 1d).…”
Section: Unbiased Proteomics Applied To Hdl Biologymentioning
confidence: 99%
“…1a). Some of these studies have specifically addressed whether proteins are differentially localized across HDL size or density fractions [2, 4, 11, 12]. …”
Section: Unbiased Proteomics Applied To Hdl Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…68 Singh et al from our laboratory, however, demonstrated the ability of PRM to measure <1% tracer enrichment in not only apoA-I from 5 HDL size fractions, but also 6 additional HDL apolipoproteins. 72 Figure 7B demonstrates a PRM scan of the apoA-I peptide, THLAPYSDELR. A magnification of a fragment ion (b4, THLA) shows its isotopes, M0-M3.…”
Section: Selected Reaction Monitoring (Srm) and Parallel Reaction Monmentioning
confidence: 99%